2020
DOI: 10.1186/s12889-020-09165-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, awareness, treatment, and control of hypertension in older people: results from the population-based KORA-age 1 study

Abstract: Background: Hypertension remains a significant modifiable risk factor for cardiovascular diseases and a major determinant of morbidity and mortality. We aimed to describe sex-stratified age-standardized estimates of prevalence, awareness, treatment and control of hypertension, and their associated factors in older adults. Methods: The KORA-Age1 is a population-based cross-sectional survey carried out in 2008/2009 on individuals aged 65-94 years in Augsburg region, Germany. Blood pressure measurements were avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
31
1
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 37 publications
8
31
1
3
Order By: Relevance
“…21 Even so, the treatment rate of hypertension in the elderly population in Shenzhen was still far below that of elderly in other countries such as the USA, Australia, Germany and Colombia. [22][23][24] Similar to other studies, we found that the treatment of hypertension was significantly higher among older, ex-smokers, non-drinkers,higher education level and those engaging in physical activity. 9 19 24 25 Participants engaged in physical activity may generally pay more attention to their health.…”
Section: Results Of Multivariate Analysis Of Factors Associated With Treatment and Control Of Hypertensionsupporting
confidence: 89%
See 1 more Smart Citation
“…21 Even so, the treatment rate of hypertension in the elderly population in Shenzhen was still far below that of elderly in other countries such as the USA, Australia, Germany and Colombia. [22][23][24] Similar to other studies, we found that the treatment of hypertension was significantly higher among older, ex-smokers, non-drinkers,higher education level and those engaging in physical activity. 9 19 24 25 Participants engaged in physical activity may generally pay more attention to their health.…”
Section: Results Of Multivariate Analysis Of Factors Associated With Treatment and Control Of Hypertensionsupporting
confidence: 89%
“…Our study revealed a higher level of treatment in individuals with comorbidities such as overweight, obesity, central obesity, diabetes and dyslipidaemia, which are common comorbidities with hypertension. 19 23 Moreover, in our study, history of CVD was highly correlated with receiving antihypertensive treatment. Other researchers have confirmed that having another medical condition, for example, diabetes or dyslipidaemia, is associated with greater awareness and treatment of hypertension.…”
Section: Results Of Multivariate Analysis Of Factors Associated With Treatment and Control Of Hypertensionmentioning
confidence: 49%
“…Hypertension control rates among NHANES nondiabetic individuals (39.01%, 95% CI 33.68-44.60) were comparable to our findings, and not dissimilar than those of NHANES diabetic individuals (40.39%, 95% CI 33.96-47.17) [24]. Another population-based cross-sectional survey found that treated hypertensives with diabetes were less likely to have controlled BP (OR 0.38, 95% CI 0.25-0.58) compared with nondiabetics [25]. Altogether, real-world data indicate that attaining BP treatment goal remains a major challenge, especially when multiple cardiovascular risk factors coexist.…”
Section: Discussionsupporting
confidence: 85%
“…Having other chronic diseases was associated with higher awareness and better control, too. In one study, people with diabetes, obesity, heart disease, and stroke were more likely to see a doctor and have their BP checked (26). In the present study, the patients who had a history of cardiovascular disease in their rst-and second-degree relatives had higher awareness and better control.…”
Section: Discussionsupporting
confidence: 41%
“…Similar results were also obtained in a survey performed on the people aged 65-94 years in Germany. In that study, 80.2% of the patients knew that they had HTN and 74.4% of the patients and 92.8% of the informed individuals took antihypertensive drugs (26). The higher awareness in the present study might result from a better access to health care.…”
Section: Discussionmentioning
confidence: 50%